SpaceScience App: Development of a Mobile Application for School Children - Ahmad, W.F.W. (Springer Science and Business Media Deutschland GmbH, 2021)
The inclusion of Science, technology, Engineering and Mathematics (STEM) in the curriculum has been a target for many countries around the world. Nevertheless, the bulk of early STEM education still relies on the conventional teaching model that reaches a subset of students. Most students have opted not to pursue STEM related studies because they are increasingly losing interest in studying STEM. This is due to the limited availability of engaging teaching strategies and resources for more productive learning in the classroom environment. The goal of this project is to research how the application of educational games can help to draw studentsâ interest in the topic of science, develop an educational game application and conduct user experience testing of the educational game application. A mobile application has been developed in the topic of Earth and SpaceScience for school students aged 10â11 years old. The application was developed using Ionic Framework, Angular 5, C#.NET and SQLExpress. An interview and a usability testing have been conducted with schoolteachers and a group of students aged 10 years old. The results showed that most students enjoyed and motivated in learning science by using the mobile application. Â© 2021, The Author(s), under exclusive license to Springer Nature Switzerland AG.